1987
DOI: 10.1097/00007611-198706000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of Interns After Being on Call

Abstract: I recently reported on a series of indepth interviews with house officers in 16 specialties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Others have reported that resident physicians sleep from zero to five hours while on call. 18,20,22,25,28,[40][41][42] Likewise, we did not include any measurement of supervision. The difference in errors we found could have been a function of fatigue, decreased supervision, or some other factor, rather than sleep deprivation.…”
Section: Limitationsmentioning
confidence: 99%
“…Others have reported that resident physicians sleep from zero to five hours while on call. 18,20,22,25,28,[40][41][42] Likewise, we did not include any measurement of supervision. The difference in errors we found could have been a function of fatigue, decreased supervision, or some other factor, rather than sleep deprivation.…”
Section: Limitationsmentioning
confidence: 99%
“…Obstetrical residents (who slept for <2 hours) had no deterioration in their skills of placing an epidural during labor regardless of level of training. 50 Post-call residents (24 hours) demonstrated no impairment in their performance in structured clinical interviews with actors posing as patients, 51 laboratory form testing, 52 or simulated suturing technique. 52 A study by Storer et al 53 assessed the effect of 24 vs 36 hours of sleep deprivation on cognitive and procedural skills of pediatric residents; there was no deterioration in cognitive skills (written knowledge examination), endotracheal intubation, or vein catheterization associated with the longer shift.…”
Section: The Effect Of Traditional Extended Shifts On Residentsmentioning
confidence: 99%
“…These SDmediated effects have been demonstrated both for physical work [8] and for resting conditions [16] as well as for different professions, which are repeatedly exposed to sleep deprivation, sleep disruption and/or shift work such as airline pilots [ 12], firefighters [ 11 ], rotating shift workers [2] or hospital physicians [4,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…In detail, these alterations of subjective well-being and psychosocial functioning include lower positive and higher negative mood scores, greater sleepiness ratings [11], fatigue and depression, changes in mood after 24 h or longer [4,9], reduced cognitive function [6], severe performance decrements 112] as well as psychological disturbances and family dysfunctions 12]. The above-mentioned impairments could be further corroborated by respective neuropsychological testing including vigilance tests, reaction time tasks and code tests [8].…”
Section: Introductionmentioning
confidence: 99%